Effectivity of microscopic test as a simple diagnostic method to detect fat malabsorption in children (Faculty of Medicine Universitas Indonesia, 2019)
BACKGROUND Lipid malabsorption causes many health problems, for example stunting, a major worldwide issue. There has not been any assessment on the effectivity of lipid microscopic test in diagnosing lipid malabsorption. This research was aimed to study the effectivity of lipid microscopic test in detecting lipid malabsorption in children. METHODS This was a cross-sectional diagnostic study that evaluated the effectivity of lipid microscopic test using Sudan III against steatocrit test as the gold standard in diagnosing lipid malabsorption. The study was done in 68 children aged 6–60 months in Cipto Mangunkusumo Hospital, Jakarta. Results of lipid microscopic test were compared with that of steatocrit test among children with lipid malabsorption and normal children. The primary endpoints of this study are the sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV). RESULTS A total of 68 children consisting of 41 boys and 27 girls were included, with a median age of 14.3 months. The most frequently found stool consistency was mushy (50%). The most common result of microscopic test, found in 42% of subjects, was positive 1. Sensitivity, specificity, PPV, and NPV of lipid microscopic test were 49.15%, 66.67%, 90.63%, and 16.67%, respectively. CONCLUSIONS Lipid microscopic test has a moderate sensitivity in diagnosing fat malabsorption and needs to be complemented with other methods such as steatocrit.